Effect of the Heat‐Moisture Treatment on the Enzymatic Susceptibility of Corn Starch Granules - Franco, Célia M. L. [UNESP]; Ciacco, César F.; Tavares, Débora Q. (Wiley, 1995)
Normal and waxy corn starches were isolated, adjusted to different levels of moisture and heated at 100°C for 16h. The heat treated starches were hydrolysed with α‐amylase and amyloglucosidase. The starch samples were studied by determining their water‐binding capacity, pasting properties, X‐ray diffraction and by optical and scanning electron microscopy. The results showed that the heat‐moisture treatment produced an increase in the degree of crystallinity of normal and waxy corn starches at the level of 18% moisture. This result, in conjunction with a significant decrease in the enzymatic susceptibility, suggested a rearrangement of the starch molecules with strengthening of the linkages within the granules. On the other hand, the heat‐moisture treatment caused a rupture with further rearrangment of linkages within the granules for normal and waxy corn starches adjusted to the 27% moisture level. This produced a certain degree of starch degradation increasing the accessible regions of the granule to amylolysis. Copyright © 1995 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim